2021
DOI: 10.3892/etm.2021.10449
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid inhibits high glucose‑induced injury in rat mesangial cells via the PI3K/Akt/FOXO3a signaling pathway

Abstract: The pathological damage of mesangial cells serves an important role in the occurrence and development of diabetic nephropathy. Ellagic acid has been reported to possess antioxidant, antitumor, antiviral and anti-inflammatory properties in several diseases, but the roles of ellagic acid in diabetic nephropathy are unclear. The main aim of the present study was to investigate the effect of ellagic acid on high glucose-induced mesangial cell damage. The results revealed that high glucose could induce the hyperpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In addition, it delays the development of chronic diseases. Research on the mechanism of glucose metabolism has shown that EA reduces serum glucose levels in rats by activating 5′AMP-activated protein kinase [ 54 ]. It also mitigates glucose-induced damage to pancreatic mesangial cells by activating the PI3K/Akt/FOXO3 signaling pathway, restoring pancreatic cell function, and reducing serum glucose concentration [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it delays the development of chronic diseases. Research on the mechanism of glucose metabolism has shown that EA reduces serum glucose levels in rats by activating 5′AMP-activated protein kinase [ 54 ]. It also mitigates glucose-induced damage to pancreatic mesangial cells by activating the PI3K/Akt/FOXO3 signaling pathway, restoring pancreatic cell function, and reducing serum glucose concentration [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It prevented the PI3K/Akt signalling pathway, which was activated by high glucose levels in mesangial cells, and then controlled the nuclear transcription activities of FOXO3 and NF-kB, which in turn prevented cell division, oxidative stress, the release of inflammatory factors, and the production of ECM. The current study offered an experimental theoretical foundation for the process by which ellagic acid lessened the harm that elevated glucose levels induced to mesangial cells [39].…”
Section: Ellagic Acidmentioning
confidence: 91%
“…It also activated different antioxidant enzymes, such as HO-1, NQO1, GST, and GSH [ 216 , 217 ]. The dysfunction of mesangial cells in diabetic nephropathy might be related to the PI3K/Akt signaling pathway activation inhibited by ellagic acid [ 218 ]. Ellagic acid treatment also triggered SIRT1 overexpression in renal tissues, which imparted renal tolerance to oxidative stress [ 214 ].…”
Section: Antioxidants and Kidney Diseasesmentioning
confidence: 99%